Soluble receptor for advanced glycation end products in physiological and pathological pregnancy - Germanová, Anna; Koucký, Michal; Hájek, Zdeněk; Pařízek, Antonín; Zima, Tomáš; Kalousová, Marta (Clinical biochemistry, 2010)
OBJECTIVE: The receptor for advanced glycation end products, RAGE, has been implicated in pathogenesis of many diseases. Soluble RAGE, sRAGE, extracellular domain of RAGE, is new biomarker. The aim of the study was to determine sRAGE levels in physiological pregnancy and their changes in pregnancies complicated by preterm labor or preeclampsia. DESIGN AND METHODS: Serum levels of sRAGE were determined in 79 healthy pregnant women, 42 pregnant women in preterm labor or with preeclampsia and 24 non-pregnant controls. RESULTS: sRAGE serum levels are decreased in physiological pregnancy compared to healthy non-pregnant controls (p<0.001). Serum sRAGE concentrations are higher in the 2nd trimester of physiological pregnancy, compared to the 1st and 3rd trimesters of pregnancy (p<0.001). sRAGE levels in women with preterm labor are decreased (p<0.05) and correlate negatively with the leukocyte count (r=-0.47, p<0.05). In women with preeclampsia, sRAGE is elevated (p<0.05) and correlates with serum creatinine concentration (r=0.54, p<0.05) and with uric acid concentration (r=0.51, p<0.05). CONCLUSION: Our results clearly demonstrate significant differences in serum sRAGE levels in physiological pregnancy and in pathological states in pregnancy, however, further studies are required demonstrate the usefulness and significance of sRAGE.
Keywords: ženské pohlaví; Female; Solubility; těhotenství; Pre-Eclampsia; Humans; lidé; Pregnancy; dospělí; předčasná porodní činnost; receptory imunologické; Obstetric Labor, Premature; Adult; Pregnancy Trimesters; trimestry těhotenství; rozpustnost; Receptors, Immunologic; preeklampsie